Domotización para el control de los sistemas de iluminación, climatización y seguridad en el edificio del bloque "b" de la Universidad Técnica de Cotopaxi extensión La Maná - Lozano Jacome, Abraham Damian (2022)
The purpose of this project is to implement a home automation system for the control of the different systems of the building of block "B" of the Technical University of Cotopaxi, La Maná extension, using a standardized home automation protocol. The home automation systems to be controlled are the lighting, air conditioning and security systems; For this, a standardized protocol was used, choosing the most appropriate for the development of the project through a comparison between different protocols existing in the market. It was possible to carry out the complete design of a system that controls all the existing systems mentioned. The objective of this implementation is to improve the quality of life and comfort, without neglecting the security of the building, as well as to properly control energy savings remotely through a mobile application.